Bone metabolism and vascular calcification - C.F. Danilevicius (Brazilian Journal of Medical and Biological Research, 2007)
Osteoporosis and atherosclerosis are chronic degenerative diseases which have been considered to be independent and whose common characteristic is increasing incidence with age. At present, growing evidence indicates the existence of a correlation between cardiovascular disease and osteoporosis, irrespective of age. The morbidity and mortality of osteoporosis is mainly related to the occurrence of fractures. Atherosclerosis shows a high rate of morbidity and especially mortality because of its clinical repercussions such as angina pectoris, acute myocardial infarction, stroke, and peripheral vascular insufficiency. Atherosclerotic disease is characterized by the accumulation of lipid material in the arterial wall resulting from autoimmune and inflammatory mechanisms. More than 90% of these fatty plaques undergo calcification. The correlation between osteoporosis and atherosclerosis is being established by studies of the underlying physiopathological mechanisms, which seem to coincide in many biochemical pathways, and of the risk factors for vascular disease, which have also been associated with a higher incidence of low-bone mineral density. In addition, there is evidence indicating an action of antiresorptive drugs on the reduction of cardiovascular risks and the effect of statins, antihypertensives and insulin on bone mass increase. The mechanism of arterial calcification resembles the process of osteogenesis, involving various cells, proteins and cytokines that lead to tissue mineralization. The authors review the factors responsible for atherosclerotic disease that correlate with low-bone mineral density.